2019
DOI: 10.1093/jcag/gwz007
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Resection of Ampullary Tumours: Long-term Outcomes and Adverse Events

Abstract: Background The management of ampullary lesions has shifted from surgical approach to endoscopic resection. Previous reports were limited by small numbers of patients and short follow-up. The aim of this study is to describe short- and long-term outcomes in a large cohort of patients undergoing endoscopic ampullectomy. Methods Retrospective study of endoscopic ampullectomies performed at a tertiary center from January 1999 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 46 publications
1
26
0
1
Order By: Relevance
“…The rate of diagnostic overestimation, leading to potentially inadequate and risky treatment, has been prospectively evaluated to be 15 % overall, and 21 % for initial low grade dysplasia diagnosis [19]. Normal intestinal mucosa or inflammatory tissue were found in post-papillectomy histological analysis in 8 % and in 13.8 % in two large retrospective series [37,41].…”
Section: Recommendationmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of diagnostic overestimation, leading to potentially inadequate and risky treatment, has been prospectively evaluated to be 15 % overall, and 21 % for initial low grade dysplasia diagnosis [19]. Normal intestinal mucosa or inflammatory tissue were found in post-papillectomy histological analysis in 8 % and in 13.8 % in two large retrospective series [37,41].…”
Section: Recommendationmentioning
confidence: 99%
“…In their abovementioned meta-analysis, Spadaccini et al [26] revealed a pooled rate of post-papillectomy bleeding of 10.6 % (95 %CI 5.2 %-13.6 %; I 2 = 61 %), with effective conservative management including endoscopic treatment for 149/156 events (95.5 %) for which data were available. In the more recent and largest retrospective studies, endoscopic treatments were performed in 69.1 % of cases (n = 56/81) and mostly successfully [20,39,41,88,89]. Reported endoscopic techniques included epinephrine injection, electrocoagulation, clip application, and APC.…”
Section: Recommendationmentioning
confidence: 99%
“…Endoscopic ampullectomy allows for a minimally invasive nonsurgical intervention option for the treatment of ampullary adenomas, however is associated with significant risk of PPB between 4.9% to 30%[ 72 - 79 ]. The considerably high incidence of PPB of 30% reported in the study by Hopper et al [ 72 ] was observed in resections of larger sized ampullary adenomas (between 40-60 mm).…”
Section: Therapeutic Endoscopic Proceduresmentioning
confidence: 99%
“…Any surgical intervention is associated with complications, among which the most frequent and threatening are perforation of the hollow organ and bleeding. At present, physical methods of haemostasis are widely used in endosurgery, creating comfortable conditions for performing the operation and obtaining, in general, positive results (1). However, it should be noted that 'cellular technologies' are gaining popularity in endosurgery of the digestive tract, including the use of blood components or blood cells with a haemostatic purpose.…”
Section: Introductionmentioning
confidence: 99%